Pengaruh Kinerja Keuangan Perbankan terhadap Return Saham pada saat Pandemi Covid-19 - Nabila Zara Zettira; Evana, Einde; Rizki Eka Putri, Widya (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2022)
This study aims to see the impact by Covid-19 on the economic. This study purpose to see the success of various government regulations and policies to contain the negative impacts on the economy as well as to seek economic recovery. The method used in this study is a quantitative research method, while the source of data used in this study is secondary data. This study uses secondary data from the 2019-2021 financial statements. The population in this study are conventional banking companies listed on the Indonesia Stock Exchange. The determination of the sample in this study amounted to 102 using the type of purposive sampling method. The data were analyzed using descriptive statistical tests, classical assumption tests, multiple regression analysis, F test model feasibility, and test T. The results of the research, show that the CAR, BOPO, LDR ratios have a positive influence on stock returns, NPL and ROA have no effect on stock returns, while Economic Conditions have a negative effect on stock returns during Covid-19.